The Effect of Leadership and Collaborations on SME Adaptability - Nopriadi Saputra; Abdul Rahmat; Deddi Fasmadhi (Jurnal Manajemen dan Organisasi, 2022)
This article attempts to elaborate the adaptability of SMEs (small medium enterprises) and effects of leadership and collaboration on SME adaptability. This article is a quantitative study with causal analysis. The collected data from 506 SMEs was analyzed by SmartPLS. The result reveals that SME flexibility influences on its resilience. Prosocial leadership and collaborative capability impact directly, positively, and significantly on SME resilience and flexibility. Collaborative capability played a mediating role on the relationship between leadership and adaptability. For being survival in embracing disruptive changes, the owners and/or managers of SMEs must apply pro-social orientation in leading business and developing collaborative capabilities simultaneously for being resilient. The novelty of this article is an elaboration of the linkage between leadership and adaptability, instead of the linkage between leadership and performance. This article strengthens the previous studies that leadership has an indirect impact on organizational performance or adaptability, it is mediated by collaborative capability.